2014
DOI: 10.1177/0269215514556297
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aquatic therapy on mobility of individuals with neurological diseases: a systematic review

Abstract: Our synthesis showed "fair" evidence supporting the use of aquatic therapy to improve dynamic balance and gait speed in adults with certain neurological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 30 publications
4
66
0
6
Order By: Relevance
“…Two reviews summarized that the water-based exercise for neurological disorder covers a wide variety, including resistance training, movement facilitation, motor control training, balance training, coordination training and other specific techniques 21,22 . They indicated that stroke patients improved significantly more in weight shifting ability, dynamic balance, and functional mobility as compared with the land-based intervention 21,22 .Ai Chi, first developed by Jun Konno in 1990s 23 , is one kind of water-based exercise emphasizing characteristics of balance training 24 . It resembles Tai Chi on land, complemented by Zen shiatzu and Watsu concepts 25 .…”
mentioning
confidence: 99%
“…Two reviews summarized that the water-based exercise for neurological disorder covers a wide variety, including resistance training, movement facilitation, motor control training, balance training, coordination training and other specific techniques 21,22 . They indicated that stroke patients improved significantly more in weight shifting ability, dynamic balance, and functional mobility as compared with the land-based intervention 21,22 .Ai Chi, first developed by Jun Konno in 1990s 23 , is one kind of water-based exercise emphasizing characteristics of balance training 24 . It resembles Tai Chi on land, complemented by Zen shiatzu and Watsu concepts 25 .…”
mentioning
confidence: 99%
“…A higher percentage of the maximum score indicates a higher quality study: <50% (weak), 50%–69% (fair), 70%–79% (good), and 80%–100% (very good). [16,17] A third reviewer was involved to resolve disagreements between the 2 reviewers.…”
Section: Methodsmentioning
confidence: 99%
“…The increased COP sway (displacement and velocity) during pool immersion may reflect decreased postural steadiness and/or greater stimuli for postural control, as a result of the postural disturbances in the aquatic environment. Aquatic therapy programs focused on balance and mobility may have contributed to reported gains in balance function in other neurological populations [3,23]. In other populations with disabilities, aquatic exercise programs have led to improvements in parameters of COP sway on dry land.…”
Section: Is the Aquatic Environment A Stimulus For Training Postural mentioning
confidence: 99%
“…Aquatic therapy has been underexplored in spinal cord injury (SCI) rehabilitation, despite the purported benefits of water immersion for the SCI population [1,2]. Although evidence supporting the positive effects of aquatic therapy on mobility among individuals with incomplete SCI (iSCI) is scarce [3], aquatic therapy has emerged as a promising approach to augment balance recovery [4]. Stevens et al (2015) reported improvements in balance function post underwater treadmill training in adults with iSCI [4].…”
Section: Introductionmentioning
confidence: 99%